Back in the saddle again: a re-examination of the fel temp reparatio Falling horseman type - Caza, Shawn (KOINON: The International Journal of Classical Numismatic Studies, 2019)
The FEL TEMP REPARATIO Falling horseman bronze coin type (FTR-FH) was introduced in 348 AD by Constantine I’s two surviving sons, Constans and Constantius II, as part of a three-denomination series of coins, all with the same reverse legend. Over the ten years that it was minted, the FTR-FH type was struck in large numbers for Constantius, and his two Caesars, Constantius Gallus and Julian, and in much smaller numbers for Constans and the usurper Magnentius.